Answer:
Don't have enough infromation to answer that.
Step-by-step explanation:
KH = 3(x + 2) + <span>3x - 4
KH = 3x + 6 + 3x - 4
KH = 6x + 2 = 44
6x = 42
x = 7
HJ = 3(x + 2)
HJ = 3(7 + 2)
HJ = 27</span>
Apply the radical rule to separate terms:
Cubicroot(-27) and cubic root(n^27)
Cubicroot(-27) = -3
Now you have -3 cubicroot(n^27)
Using the exponent rule
N^27 can be rewritten as (n^9)^3
Now you have -3 cubicroot((n^9)^3)
The cubic root and the 3rd power cancel out to get the final answer of
-3n^9
Answer:
$4.80
Step-by-step explanation:
Make a proportion
$12 for 2.5 pounds, and $x for 1 pound
12/2.5=x/1
x/1 is equivalent to x
12/2.5=x
Divide
x=4.8
So, one pound of peanuts costs $4.80
True, Integers mean "whole", and it cannot be a fraction or decimal
hope this helps